Portrait of a couple - Sahl, Ted (photographer):::Creator::::::::::::
Portrait of an unidentified couple, wearing formal clothing. The female is wearing an evening gown, and the male is wearing an embellished suit with a rhinestone collar, cuffs and epaulets.